A tectônica do metal na Arquitetura: estudos de caso no nordeste brasileiro - Marinho, Érika Ferreira (2022)
This research had as its central theme the tectonic analysis of metal in contemporary architectural constructions and the manner of how the technical-expressive resources that this material enables are used based on the climate and location. Understanding that the tectonics character of architecture, composed of interactions between expressiveness and materiality, results also from bioclimatic strategies adopted considering the climatic characteristics of the site. When observing the scenery of the national architectural production in the last decades, it was verified the increscent use of metal as a construction material, mainly in support structures of the architectural form in the most varied buildings, becoming important to study the existing relation between the use of this material and the bioclimatic strategies adopted whereas when united are determinants of the formal structure, being able to praise the tectonic character of architecture from the expressive possibilities of this union. Therefore, the research started from the premise that metal can be used on architecture as expressive material and technological resource that makes possible the adoption of bioclimatic strategies, having as main objective to analyze the metal tectonic in contemporary architectural constructions built on the Brazilian Northeast, in a hot and humid climate since the 1990 decade, to verify if the technical-expressiveness resources that this material enable are used properly to the climate and location characteristics. After a bibliographic review around the main concepts that permeate these themes, parameters of analytical tectonics were set in consonance with the bioclimatic strategies for hot and humid climate in order to observe the validity or otherwise of the premise. Reference architectural works with different programs and specific solutions were elected for the tectonic analysis, in which predominated the use of metal in their formal structure, designed by architects of recognized competence on a local, national and international level, as: the building that housed the Peugeot dealership (1996) in João Pessoa/PB - designed by the architect Gilberto Guedes; the hospital of Sarah Kubitschek (1994) in Salvador/BA, by architect João Filgueiras “Lelé” Lima and the Morro Arena in the city of Natal/RN, conceived by the swiss office Herzog & De Meuron. From the analysis, it was proven that a architectonic quality was reached by the exploitation of the expressive potentialities of metal in consonance with the use of proper bioclimatic strategies for the hot and humid climate, reinforcing the possibility of alignment between the expressiveness arising from architectonic materiality and suitability of the location and climate characteristics.